Applications of statistical physics in finance and economics - Thomas Lux (Kiel University, Department of Economics, 2007)
This chapter reviews recent research adopting methods from statistical physics in theoretical or empirical work in economics and nance. The bulk of what has recently become known as 'econophysics' in broader circles draws its motivation from observed scaling laws in nancial markets and the abundance of data available from the economy's nancial sphere. The rst part of this review presents the robust power laws encountered in nancial economics and discusses potential explanations for scaling in nance derived from models of stochastic interactions of traders. Sec. 3 provides an overview over other applications of statistical physics methodology in nance and attempts to evaluate the impact they have had so far on nancial economies. With the following section, the review turns to recent work on the emergence of wealth and income heterogeneity and the recent inception of new strands of research on this topic both within econophysics and the neoclassical economics tradition. The third part reviews the new stylized facts that have been identi ed in cross-sectional data of rm characteristics and agent-based approaches to industrial organization and macroeconomic dynamics that have been motivated by these ndings. We conclude with an assessment of the major methodological contributions of this new strand of research.
Keywords: 330; Econophysics; Finanzmarkt; Wirtschaftstheorie; Agent-based Model; Querschnittsanalyse; Theorie